Reconstruction of the diagenetic environments of tight sandstone reservoirs; a case study from the Tengger Formation in the Baiyinchagan Sag, Erlian Basin, northern China - Li Shengyu, Li Shengyu; Tian Jingchun, Tian Jingchun; Lin Xiaobing, Lin Xiaobing; Yin Nanxin, Yin Nanxin; Luo Chao, Luo Chao; Yang Dongdong, Yang Dongdong (Lithosphere, 2022)
The Lower Cretaceous Tengger Formation located in the Baiyinchagan Sag of the Erlian Basin comprises mainly deeply buried tight sandstone. The identification of high-quality reservoirs in these thickly stacked and heterogeneous units requires a comprehensive understanding of the diagenetic environmental history of the rocks. This paper reports an integrated study involving thin-section petrography, scanning electron microscopy, X-ray diffraction, fluid-inclusion analysis, and vitrinite reflectance analysis of Tengger Formation sandstones with the aim of characterizing the diagenetic conditions of the reservoir rocks and providing guidance for future petroleum exploration. Observed mineral assemblages, the distribution of authigenic minerals, and the distribution and nature of pores suggest the presence of two types of diagenetic environment, acidic and alkaline, which have varied over time and vertically through the rock column. Acidic conditions are indicated by quartz overgrowths and dissolution of both feldspar and carbonate cement. In contrast, alkaline conditions are indicated by the precipitation of carbonate cement, feldspar overgrowths, quartz dissolution, and occurrences of authigenic illite and chlorite. Changes in pore fluid chemistry controlled the evolution of the diagenetic environment. The early diagenetic environment from 110 Ma to 107 Ma was syndepositional and thus controlled by the chemistry of water in depositional centers, which is interpreted to have been weakly alkaline. Significant burial that occurred at 107 Ma induced pulses of hydrothermal fluids and petroleum into the reservoir rocks, which caused a shift to an acidic diagenetic environment. From 103 Ma to 70 Ma, subsequent episodes of uplift and burial caused periodic alternation between acidic and alkaline diagenetic environments. Three distinct episodes of oil and gas charging interpreted from petrography and the homogenization temperatures of fluid inclusions played a critical role in the enhancement of porosity through time. From 70 Ma to the present, acidic diagenesis gradually weakened because of the consumption of organic acids during the process of interaction between rocks and fluids. This study demonstrates the importance of understanding the diagenetic history of reservoir rocks and provides the basis for improved reservoir characterization and optimized hydrocarbon exploration of the Tengger Formation.